Hubungan Postur Kerja dan Masa Kerja dengan Nyeri Muskuloskeletal (Analisis pada Pekerja Pembuat Batu Bata di Desa Karangsono Kecamatan Mranggen Kabupaten Demak) - Siti Hardiyati; Merry Tiyas Anggraini; Wijayanti Fuad (Universitas Muhammadiyah Semarang, 2022)
Background: The musculoskeletal pain is often found in workers who prioritize physical ability when working, for example brick makers. Objective: The purpose of this study is to analyze the relationship between work posture and work period with the risk of musculoskeletal pain in brick makers in Karangsono Village, Mranggen District, Demak Regency.Method: This study used analytic observation method with cross sectional approach. Subjects were taken by total sampling=45 workers. Data were analyzed with Chi Square/fisher's exac testt. The research instrument used the REBA for measuring work posture, NBM for the muculoskeletal pain. Result: Correlation between work posture with the musculoskeletal pain has p value=0.017 (p<0.05), with a prevalence ratio (RP)=7,000 Confidence Interval (95% CI) 1.423-34,434. The correlation between work period with the musculoskeletal pain has pvalue p=0.044 (p<0.05), with a prevalence ratio (RP)=4.941 Confidence Interval (95% CI) 0.944-25.875. Conclusion: There is a significant correlation between work posture and work period with the musculoskeletal pain. Work postures with high and very highrisk levels will be at risk of causing musculoskeletal pain and work period of 5 years is causing higher risk of musculoskeletal pain.